Extracorporeal cardiopulmonary resuscitation among patients with out-of-hospital cardiac arrest - Choi, Dae-Hee; Kim, Youn-Jung; Ryoo, Seung Mok; Sohn, Chang Hwan; Ahn, Shin; Seo, Dong-Woo; Lim, Ju Yong; Kim, Won Young (Clinical and experimental emergency medicine, 2016)
Extracorporeal cardiopulmonary resuscitation (ECPR) may be considered as a rescue therapy for patients with refractory cardiac arrest. Identifying patients who might benefit from this potential life-saving procedure is crucial for implementation of ECPR. The objective of this study was to estimate the number of patients who fulfilled a hypothetical set of ECPR criteria and to evaluate the outcome of ECPR candidates treated with conventional cardiopulmonary resuscitation. We performed an observational study using data from a prospective registry of consecutive adults (≥18 years) with non-traumatic out-of-hospital cardiac arrest in a tertiary hospital between January 2011 and December 2015. We developed a hypothetical set of ECPR criteria including age ≤75 years, witnessed cardiac arrest, no-flow time ≤5 minutes, low-flow time ≤30 minutes, refractory arrest at emergency department >10 minutes, and no exclusion criteria. The primary endpoint was the proportion of good neurologic outcome of ECPR-eligible patients. Of 568 out-of-hospital cardiac arrest cases, 60 cases (10.6%) fulfilled our ECPR criteria. ECPR was performed for 10 of 60 ECPR-eligible patients (16.7%). Three of the 10 patients with ECPR (30.0%), but only 2 of the other 50 patients without ECPR (4.0%) had a good neurologic outcome at 1 month. ECPR implementation might be a rescue option for increasing the probability of survival in potentially hopeless but ECPR-eligible patients.